Good Governance in Environmentally Friendly Energy Management: Case Study of the Gas Network Program (Jargas) in Bojonegoro, Indonesia - Sulistyaningrum, Ajeng; Suprastiyo, Ahmad; Kasiami, Sri (Publik : (Jurnal Ilmu Administrasi), 2024)
Based on oil and gas reserve data, the Bojonegoro Regency government has the potential to build a gas distribution network for households (JARGAS) which is useful for reducing the use of petroleum. The Regent of Bojoengoro and 17 and the mayor, signed a memorandum of understanding with the Director General of Oil and Gas, Ministry of Mineral Resources (ESDM) for the provision and distribution of natural gas through the gas network. This study examines the role of Good Governance in environmentally friendly energy governance through a case study of the Jargas Program in Bojonegoro, which aims to replace LPG with clean energy. With a descriptive qualitative method, data will be collected through observation and interviews with stakeholders such as the regional government of the Economy and Natural Resources Section of the Bojonegoro Regional Secretariat, PT PGN Area Bojonegoro, and the community in Bojonegoro and secondary sources such as publications. This study examines the application of Good Governance principles, such as transparency, accountability, openness, and the rule of law. The study results indicate that strategic steps are needed to improve information transparency, transparency of use, and accountability from the regional government to expand access to gas networks to be more effective, transparent, and meet community needs. In conclusion, implementing Good Governance supports the sustainability of clean energy, but it is necessary to strengthen community participation and active socialization.